Etika bisnis Islam: Etika bisnis dan pemeliharaan lingkungan - Maulina, Anisa Turrohmatul (Maliki Interdisciplinary Journal, 2024)
Ethics is an action carried out by an individual or group that is based on values ​​and morals. In business activities, good ethics are also needed. Meanwhile, business is an activity obtained for profit. Ethics in business has a role, that is, for decisions made, moral awareness is very necessary. In this era of globalization, many businesses are being developed, one of which is the e-commerce business. One of the successes of an e-commerce business is consumer trust. Therefore, e-commerce businesses require ethics and social responsibility. The research aims to analyze business ethics and social responsibility, namely the Smooth Fashion Shop, Blitar using descriptive methods through question and answer, observation, and documentation based on existing facts, and also using literature methods. Based on the research results, Blitar fashion stores implement ethics in business and social responsibility, namely using photos based on existing facts.